Circulating miRNA Expression Profiling in Primary Aldosteronism - Decmann, Abel; Nyírö, Gábor; Darvasi, Ottó; Turai, Péter; Bancos, Irina; Kaur, Ravinder Jeet; Pezzani, Raffaele; Iacobone, Maurizio; Kraljevic, Ivana; Kastelan, Darko; Parasiliti-Caprino, Mirko; Maccario, Mauro; et al. (Frontiers in Endocrinology, 2019)
Objective: Primary aldosteronism is a major cause of secondary hypertension. Its two principal forms are bilateral adrenal hyperplasia and aldosterone-producing adenoma whose differentiation is clinically pivotal. There is a major clinical need for a reliable and easily accessible diagnostic biomarker for case identification and subtyping. Circulating microRNAs were shown to be useful as minimally invasive diagnostic markers. Our aim was to determine and compare the circulating microRNA expression profiles of adenoma and hyperplasia plasma samples, and to evaluate their applicability as minimally invasive markers. Methods: 123 samples from primary aldosteronism patients were included. Next-generation sequencing was performed on 30 EDTA-anticoagulated plasma samples (discovery cohort). Significantly differently expressed miRNAs were validated by real-time reverse transcription-qPCR in an independent validation cohort (93 samples). Results: We have found relative overexpression of miR-30e-5p, miR-30d-5p, miR-223-3p and miR-7-5p in hyperplasia compared to adenoma by next-generation sequencing. Validation by qRT-PCR confirmed significant overexpression of hsa-miR-30e-5p, hsa-miR-30d-5p and hsa-miR-7-5p in hyperplasia samples. Regarding the microRNA expressional variations, adenoma is more heterogeneous at the miRNA level compared to hyperplasia. Conclusion: Three microRNAs were significantly overexpressed in hyperplasia samples compared to adenoma samples, but their sensitivity and specificity values are not good enough for introduction to clinical practice.